Hydrophobic gasket mutation produces gating pore currents in closed human voltage-gated proton channels - Banh, Richard; Cherny, Vladimir V.; Morgan, Deri; Musset, Boris; Thomas, Sarah; Kulleperuma, Kethika; Smith, Susan M. E.; Pomès, Régis; DeCoursey, Thomas E. (Proceedings of the National Academy of Sciences - PNAS, 2019)
The hydrophobic gasket (HG), a ring of hydrophobic amino acids in the voltage-sensing domain of most voltage-gated ion channels, forms a constriction between internal and external aqueous vestibules. Cationic Arg or Lys side chains lining the S4 helix move through this “gating pore” when the channel opens. S4 movement may occur during gating of the human voltage-gated proton channel, hHV1, but proton current flows through the same pore in open channels. Here, we replaced putative HG residues with less hydrophobic residues or acidic Asp. Substitution of individuals, pairs, or all 3 HG positions did not impair proton selectivity. Evidently, the HG does not act as a secondary selectivity filter. However, 2 unexpected functions of the HG in HV1 were discovered. Mutating HG residues independently accelerated channel opening and compromised the closed state. Mutants exhibited open–closed gating, but strikingly, at negative voltages where “normal” gating produces a nonconducting closed state, the channel leaked protons. Closed-channel proton current was smaller than open-channel current and was inhibited by 10 μM Zn2+. Extreme hyperpolarization produced a deeper closed state through a weakly voltage-dependent transition. We functionally identify the HG as Val109, Phe150, Val177, and Val178, which play a critical and exclusive role in preventing H⁺ influx through closed channels. Molecular dynamics simulations revealed enhanced mobility of Arg208 in mutants exhibiting H⁺ leak. Mutation of HG residues produces gating pore currents reminiscent of several channelopathies.